"Feminismo ideal e sadio" : os discursos feministas nas vozes das mulheres intelectuais capixabas, Vitória/ES (1924 a 1934) - Rangel, Lívia de Azevedo Silveira (2011)
As a subject matter, this work has the construction process of feminists' discourse through espírito-santeses intelectual women's textual production who acted as contributor in Vida Capichaba magazine, during the period from 1924 to 1934. The purpose was to identifty specific things on those feminists' manifestations, especially those related to sociocultural matters in Vitória city. Those particular features had helped, among other things, to highlight differences both internally and externally. Externally in comparison with nationally knowed feminists, as Bertha Lutz, and internally, identifing a plural discourse on the subject. The research had shown the existence of at least three different lines of thought that tried to call reader's attention: the "Ideal and healthy" feminism, a moderate discourse, the advanced feminism, a more controversial one, and the diffuse feminism, which vacillate between both. Moreover, the research had shown that the moderate feminism became more popular, a preference that can be proved by analizing the frequency of publication in Vida Capichaba magazine, as well as for its high public acceptance.